2011
DOI: 10.1074/jbc.m111.224832
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NocL Involved in Thiopeptide Nocathiacin I Biosynthesis

Abstract: The radical S-adenosylmethionine (AdoMet) enzyme superfamily is remarkable at catalyzing chemically diverse and complex reactions. We have previously shown that NosL, which is involved in forming the indole side ring of the thiopeptide nosiheptide, is a radical AdoMet enzyme that processes L-Trp to afford 3-methyl-2-indolic acid (MIA) via an unusual fragmentation-recombination mechanism. We now report the expansion of the MIA synthase family by characterization of NocL, which is involved in nocathiacin I biosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
2
33
1
3
Order By: Relevance
“…9 A highly similar enzyme, NocL, from the nocathiacin biosynthetic pathway has also been characterized. 79 …”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…9 A highly similar enzyme, NocL, from the nocathiacin biosynthetic pathway has also been characterized. 79 …”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…A unique feature of the NosL/NocL in vitro assay is that a substantial amount of the shunt product (3-methylindole) is produced in addition to the authentic product (MIA). Interestingly, the production of 3-methylindole, presumably by inadvertent trapping of the indolyl intermediate resulting from C␣-C␤ cleavage, is actually adjustable by changing the reductant sodium dithionite concentration in the assay (42,43). Combined with the detection of another shunt product (glyoxylate) in the reaction, these observations firmly established a fragmentation-recombination mechanism that is involved in MIA synthesis.…”
Section: -Methyl-2-indolic Acid (Mia) Synthase Nosl/nocl In Thiopeptmentioning
confidence: 63%
“…The homolytic cleavage of the C␣-C␤ bond of the tryptophan radical, resulting in 3-methyleneindole and a glycyl radical, is supported by computational studies and has been confirmed by trapping the glycyl radical as a glycine-dansyl derivative by a rapid-quench method (42). The putative glycyl radical has been observed by EPR spectroscopy during the steady-state phase of NocL catalysis (43). In contrast to the relatively well understood fragmentation mechanism, little is known about the subsequent recombination process by which the two 3-methyleneindole and glycyl radical fragments are tailored to afford MIA and the coproducts formaldehyde and ammonia.…”
Section: -Methyl-2-indolic Acid (Mia) Synthase Nosl/nocl In Thiopeptmentioning
confidence: 71%
See 1 more Smart Citation
“…[86] Bemühungen, mit dem isolierten Enzym NosL andere vom Trp abgeleitete Indolsäurederivate als das fluorierte zu erzeugen, schlugen fehl. Dieses Enzym ist für die Transformation von Trp zu 3-Methylindolsäure verantwortlich, [87] aber diese Resultate gehen auf seine hohe Substratspezifität zurück, die die Zahl der mit dieser Strategie darstellbaren Analoga stark begrenzt. Um ein 6'-fluoriertes Thiostreptonanalogon darzustellen, wurde einer Kultur mutierter S.-laurentii-Zellen, denen das Gen tsrT fehlte, das Chinaldinsäurederivat 34 zugesetzt.…”
Section: Analoga-bildung In Vivounclassified